2017
DOI: 10.1126/scitranslmed.aan0972
|View full text |Cite
|
Sign up to set email alerts
|

A glucagon-like peptide-1 receptor agonist reduces intracranial pressure in a rat model of hydrocephalus

Abstract: Current therapies for reducing raised intracranial pressure (ICP) under conditions such as idiopathic intracranial hypertension or hydrocephalus have limited efficacy and tolerability. Thus, there is a pressing need to identify alternative drugs. Glucagon-like peptide-1 receptor (GLP-1R) agonists are used to treat diabetes and promote weight loss but have also been shown to affect fluid homeostasis in the kidney. We investigated whether exendin-4, a GLP-1R agonist, is able to modulate cerebrospinal fluid (CSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 51 publications
1
88
0
3
Order By: Relevance
“…We also detected LUXendin645labelling in the CP, an epithelial-vascular structure that secretes cerebrospinal fluid (CSF). Rat CP has recently been shown to express GLP1R ex vivo, with Ex4 reducing intracranial pressure in hydrocephalic models 52 . Notably, super-resolution snapshots showed that GLP1R in the ARC, AP, and CP were organized as nanodomains at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected LUXendin645labelling in the CP, an epithelial-vascular structure that secretes cerebrospinal fluid (CSF). Rat CP has recently been shown to express GLP1R ex vivo, with Ex4 reducing intracranial pressure in hydrocephalic models 52 . Notably, super-resolution snapshots showed that GLP1R in the ARC, AP, and CP were organized as nanodomains at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Along with functional changes in the fusiform gyrus, lixisenatide injection also differentially altered the functional activation in the lateral ventricle, which appeared to occur in the region of the choroid plexus [56] in lean and obese individuals with T2DM. In adult mice, the choroid plexus supports the recruitment and proliferation of neural stem cells [57] and expresses receptors for several hormones, including GLP-1 [58] and leptin [59]. The GLP-1 receptors in the choroid plexus are involved in the modulation of CSF [58], but their metabolic role is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In adult mice, the choroid plexus supports the recruitment and proliferation of neural stem cells [57] and expresses receptors for several hormones, including GLP-1 [58] and leptin [59]. The GLP-1 receptors in the choroid plexus are involved in the modulation of CSF [58], but their metabolic role is unknown. The choroid plexus also plays a role as a barrier or transporter in the brain along with the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of significant brain edema, elevated intracranial pressure, and alteration in brain metabolism have been reported to occur in in the setting of repetitive mild head trauma, 45,71 but there is no evidence that significant elevations in intracranial pressure occur in mild TBI in general. 73 These findings raise the possibility that brain swelling and its potential adverse consequences including PTH could be treated acutely and/or chronically with well tolerated oral or parental approaches. Based in part upon this hypothesis, one study evaluated the effects of hypertonic saline on headache and other symptoms following concussion in children.…”
Section: Basic Mechanisms Of Pth As Targets For Therapymentioning
confidence: 99%
“…72 Recent studies in animal models have identified a novel strategy for the reduction of intracranial hypertension based on targeting the GLP-1 receptor. 73 These findings raise the possibility that brain swelling and its potential adverse consequences including PTH could be treated acutely and/or chronically with well tolerated oral or parental approaches.…”
Section: Basic Mechanisms Of Pth As Targets For Therapymentioning
confidence: 99%